Motivation for Participating and Performing in English Classrooms: Between Self-images and Positioning - Shanthi Nadarajan; Nurulhuzaiman Hussain; Damien Mikeng (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
Second language learning motivation is often analyzed as a multidimensional construct involving learner’s images of their individual selves and complex statistical measures. While many of these analysis have deepened understanding of various cognitive and affective factors influencing language learner behavior, research investigating the different motivation factors that combine learner types remains scarce. Involving 78 Malaysian undergraduates from a University in East Malaysia taking a proficiency course, the study looked at learner motivation in relation to L2 motivational dimensions, classroom factors and learning goals. An exploratory cluster analysis identified 4 group motivational profiles: 1-motivated, 2-amotivated, 3-externally motivated and 4-self-determined. Initial data analysis found both learner images (the ideal L2 learner) and instrumental (Ought to L2 learner) as main factors influencing motivated learning behavior. The combined findings for learner confidence in the classroom and vitality of L2 speaker communities revealed that except for the extrinsically motivated communities (e.g. International Finance students), most students indicated learning as more meaningful if attention was given to their first language resources. Classroom activities that integrate first language resources  have a positive influence on learner’s effort and willingness to invest while a strict L2-only perspective have a negative effect on learner motivation. Given the role of English for the digital world, L2 universities may benefit from including learners’ first language resources and experience for engaging and helping learners to perform academically.